Core process representation in power system operational models: Gaps, challenges, and opportunities for multisector dynamics research. (1st January 2022) - Oikonomou, Konstantinos; Tarroja, Brian; Kern, Jordan; Voisin, Nathalie
Abstract: Power grid operations increasingly interact with environmental systems and human systems such as transportation, agriculture, the economy, and financial markets. Our objective is to discuss the modelling gaps and opportunities to advance the science for multisector adaptation and tradeoffs. We focus on power system operational models, which typically represent key physical and economic aspects of grid operations over days to a year and assume a fixed power grid infrastructure. Due to computational burden, models are typically customized to reflect regional resource opportunities, data availability, and applications of interest. We conceptualize power system operational models with four core processes: physical grid assets (generation, transmission, loads, and storage), model objectives and purpose, institutions and decision agents, and performance metrics. We taxonomize the representations of these core processes based on a review of 23 existing models. Using science questions around grid and short term uncertainties, long term global change, and multisectoral technological innovation as examples, we report on tradeoffs in process fidelity and tractability that have been adopted by the research community to represent multisectoral interactions in power system operational models. Our recommendations for research directions are model-agnostic, focusing on core processes, their interactions with other human systems, and consider computational tradeoffs. Highlights: 23 power system operational models are reviewed to develop a process-based taxonomy. The taxonomy of core process representations is model agnostic. We discuss key core process representation and computational tradeoffs by science question. We identify technical gaps and opportunities to support multisector dynamics research.